Peran Broadcasters dan Brand Image dalam Meningkatkan Loyalitas Konsumen — Bukti dari Live Streaming di Platform E- commerce Shopee - Gugyh Susandy; Rizal Septiana (STIESA Press, 2025)
This study aims to analyze the role of Broadcasters and Brand Image in enhancing consumer loyalty on the Shopee e-commerce platform, particularly through the live streaming feature. This research employs a quantitative method with a descriptive approach, involving 100 respondents who are users of Shopee Live in Subang Regency and customers of the